Clonal Propagation of Two Clones Eucalyptus Pellita F. Muell By Mini-Cutting - Ellok Dwi Sulichantini; Maman Sutisna; Sukartiningsih Sukartiningsih; Rusdiansyah Rusdiansyah (International Journal of Science and Engineering, 2014)
Eucalypt is known as the fastest growing tree species in the world. Some advantages such as fast growing, hight yielding, short rotation, less desease, lots of purposes and good economic benefit have made Eucalypt as the most important forest tree product for industrial raw material in Indonesia. However, those advantages of Eucalypt including fast growing, high yielding, short rotation and less desease can only be achieved through selecting a good clone. Cutting propagation is considered as one of the main methode to produce good seedling. Sprouts of two clones of Eucalyptus pellita F. Muell (E. 13 and E. 77) were collected from mini hedge. Total of 1080 of each clone was planted in greenhouse. The result showned that Clone E. 77 was better than E. 13 in term of growth of rooting, the increment of height, stem diameter and number of leaves at 60 and 75 days after planting